Educational and Historical Contexts of Villa Konczakówka in Brenna - Marzena Bogus-Spyra (Sport i Turystyka)
Villa Konczakówka, also known as a hunters’ manor, is situated in the town of Brenna. It is regarded as a tourist attraction also because it is a listed heritage building with educational potential. The place was built nearly 100 years ago through the efforts of Brunon Konczakowski, a Cieszyn-based collector and iron merchant, who kept his family’s passion for game hunting and, in 1927, began to buy land properties, which included a forester’s lodge on the slope of Mount Czupel in Głębiec (Brenna). The Tyrolean-style villa was built of larch and Swiss pine wood without using a single nail. Its construction began in the spring of 1929 and was completed in the same year’s December. The place became a venue for social meetings, not only for people involved in the game hunting activities taking place there. The interior of the building, decorated according to the owner’s ideas, closely matches the owner’s interests, namely collecting works of art and hunting trophies. Although the rooms have been heavily stripped of exhibits, the glory days of the place can still be experienced there through Swiss pine furniture, wall-mounted paintings and countless hunting trophies, which can now be used for educational purposes. For example, one can see what the capercaillie, an extremely rare breeding bird, at risk of extinction in Poland, looks like. Visitors to Villa Konczakówka are invariably greeted by the original host of this place, whose silhouette is immortalised in a wooden sculpture hanging from the ceiling. A separate building belonging to the property is the neo-Gothic chapel of Saint Hubertus, built of locally quarried sandstone.